1990
DOI: 10.1007/bf02789141
|View full text |Cite
|
Sign up to set email alerts
|

Distributional pattern of zinc, cadmium, mercury, and selenium in livers of Hooded Seal (Cystophora cristata)

Abstract: The liver of Hooded Seal (Cystophora cristata) consists of six lobes of unequal sizes. Extensive sampling by means of cutout samples covering the depth horizon 2-30 mm below liver surface indicates that the liver may be considered homogeneous as to concentrations of zinc, cadmium, mercury, and selenium (residuals of overall mean compatible with normality, the all-organ variance negligibly in excess of within-lobe variance). Mercury and selenium are present in equimolar concentrations. Cutout samples have mercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Moreover, many studies have reported Hg and Se to be correlated in a molar ratio of 1:1, as in HgSe (e.g. Koeman et al 1973, Nielsen & Dietz 1990, Wagemann et al 1998. The molar ratio of Hg:Se in the liver of grey seals from the Faroe Islands was ~1 (Fig.…”
Section: Toxicological Aspectsmentioning
confidence: 96%
“…Moreover, many studies have reported Hg and Se to be correlated in a molar ratio of 1:1, as in HgSe (e.g. Koeman et al 1973, Nielsen & Dietz 1990, Wagemann et al 1998. The molar ratio of Hg:Se in the liver of grey seals from the Faroe Islands was ~1 (Fig.…”
Section: Toxicological Aspectsmentioning
confidence: 96%
“…HgSe granules (tiemannite) have been identified in the liver of seabirds, marine mammals and humans (Martoja & Berry 1980, Pelletier 1985, Hansen et al 1989, Nigro & Leonzio 1996. Moreover, many studies also reported that Hg and Se are correlated in a 1:1 molar ratio as in HgSe (Koeman et al 1973, Nielsen & Dietz 1990, Law et al 1997, Wagemann et al 1998. G. macrorhynchus and K. breviceps from New Caledonia had a Hg:Se molar ratio close to 1 and a low percentage of organic Hg in liver (Fig.…”
Section: Detoxification Processesmentioning
confidence: 98%
“…As a result, the pH of the intestine reduces. In acidic pH, inorganic calcium [27,28,29], magnesium [29], iron [27], manganese [36], magnesium [37], boron [38], and copper and zinc [39] salts become soluble. This process promotes the colonic absorption of inorganic minerals to the gut.…”
Section: Osteoporosismentioning
confidence: 99%